CESifo Forum Special Issue April 2013: Target Balances and the Crisis in the Euro Area - Philippine Cour-Thimann (CESifo Forum, 2013)
This paper offers a meticulous description and analysis of the development of the Target balances, with a rich set of new data and detailed information that specialists will treasure and the general public will find illuminating. The last part of the paper, in which the author discusses measures to prevent Target balances from ballooning in the future and includes a comparison of settlement possibilities, is particularly thoughtprovoking and useful. In the US system, balance-of-payment imbalances between commercial banks and, much later, district Feds, were settled for two hundred years using gold and gold certificates; and the US system only recently adopted settlement with marketable securities. In Europe no settlement procedure for Target balances has been introduced to-date. Target balances are merely carried forward on the balance sheets of national central banks from year to year, with interest added to the debt and liability positions that have accumulated between the national central banks. This could imply risks that limit the policy choices of member countries. After all, Moody's decided to consider downgrading the Netherlands and Germany because of their huge outstanding Target claims. It is high time for the Eurosystem partners to discuss the settlement issue more seriously.
Keywords: 330